Variation in tensile strength with eb-crosslinking of hybridized kenaf/palf reinforced hdpe composite - Aji, Suleiman; Zainudin, Edi Syam; Mohd Dahlan, Khairul Zaman; Abdan, Khalina; Salit, Mohd Sapuan (2011)
Hybridized Kenaf/PALF reinforced HDPE composite was fabricated and characterized. Kenaf and PALF fiber were treated with 1,2 and 3% concentrations of Silane and TMPTA followed by treatment with various electron beam irradiation (EBI) dose. The effects of EBI on the tensile properties of treated and untreated composites were compared. The composites were prepared by mixing the fibres and the HDPE in a Brabender plasticod at 190 c for 25 minutes at 40rpm. Tensile specimen were cut out from sheet produced by compression molding operation. These specimens were then irradiated using a 2.0 MeV electron beam machine at dose range of 10,20,30,40,60,80 and 100kGy at the instance of composite without crosslinking agents. Thereafter, 10kGy was selected to irradiate specimen that was prepared with 1,2 and 3%wt of Silane and TMPTA in order to see its effect on the hybrid. Hybrid irradiated without the addition of any crosslinking agent showed increase in tensile strength and modulus with increase in radiation dose. Generally, both hybrids responded marginally to the crosslinkers used. HDPE could have served as a crosslinker, making Silane and TPMta ineffective, thus, radiating composite without their addition is preffered. Fractured surfaces of the composites, examined by a scanning electron microscope showed good adhesion between the fiber and matrix.